Experimental Study of Neodymium (Nd3+) Doped Mn-Ni based Spinel Ferrite (Mn0.5Ni0.5NdxFe2-xO4) Nanoparticle using Sol-Gel Method - Gilani , Zaheer Abbas; Tariq, Muhammad Waqas; Khan Asghar, H. M. Noor ul Huda; Khan, Naeem (Journal of Materials and Physical Sciences, 2021)
Neodymium (Nd3+) doped Mn-Ni based spinel ferrite with composition of Mn0.5Ni0.5NdxFe2-XO4 (x= 0.00, 0.5, 0.10, 0.15 and 0.20), the nanoparticle was essentially formulated by sol-gel self-ignition method. The impact of Nd3+ doping on structural and electrical properties has been extensively studied. XRD verified the FCC spinel arrangement of the synthesized samples. The Debye Scherer formula is used to determine the crystalline size, which was observed in the nano scale ranging between 6 and 10 nm. XRD was used to validate the composition, crystalline size and determining different structural parameters of sample. It is noted that the lattice parameter changes when the Nd3+ doping concentration was enhanced because smaller radius of Fe3+ ions is replaced by large ionic radius of Nd ions. When Nd concentration raises X-Ray density and dislocation density also rises. FTIR verify the compositions of spinel phase and also examine the absorption bands. There were two major frequency bands one was high frequency band ?1 with range of about 500cm-1. Second was low frequency band ?2 with range of about almost 400cm-1. Dielectric performed in the frequency range of 1 MHz to 3 GHz. It was used to determine the effect of Nd3+ doping on various parameters. Dielectric investigations showed decline in dielectric constant. Impedance analysis revealed reducing values with frequency, due to the increase in material conductivity. Real and imaginary modulus study showed the influence of grain boundaries at low frequencies. These properties played significant role in high frequency applications and semiconductor devices.